Changes in the structure and composition of nano-sized Ni-Cu multilayer films with increasing temperature in an atmosphere with and without hydrogen - Hioki, T.; Iwamura, Y.; Itoh, T.; Saito, M.; Yamauchi, S.; Takahashi, T.; Kasagi, J. (Frontiers in Materials, 2024)
For a system of a nano-sized Ni-Cu multilayer on a Ni substrate and hydrogen gas, many experimental results suggest an anomalous heat release that may be caused by low-energy nuclear reactions in condensed matter. In this paper, to clarify the structural change of the Ni-Cu multilayer with increasing temperature up to 900°C in an atmosphere with and without hydrogen, an in-situ X-ray diffraction (XRD) study using synchrotron radiation was performed for a system of 6 × {Ni(14 nm)/Cu(2 nm)}/α-SiO2(10 nm)/Si wafer (0.5 mm). The surface morphology observation and elemental analysis for the samples after the XRD measurements were performed using electron microscopy analyses. The XRD peaks from Ni were observed up to 600°C and satellite peaks were observed at 300–600°C, which indicates that the initial multilayer structure with a sharp interface was maintained up to approximately 600°C regardless of the atmosphere. After the temperature had increased to 900°C, the initial Ni-Cu multilayer became a single-layer of Ni-Cu alloy with the nominal composition when the system was heated in an atmosphere containing hydrogen; in a hydrogen-free atmosphere, it became a modified Ni-Cu multilayer, where the thickness of the Cu layer decreased to half of the initial value, and many particles were randomly distributed on the surface. For the Ni-Cu multilayer system, a baking pre-treatment at high temperatures in a hydrogen-free environment is considered advantageous to stimulate the anomalous heat effect if we assume that hydrogen diffusion through the bimetallic interface is one of the key factors that induce anomalous heat generation.